Trzy krolowe : szkice brytyjskie - Jaszunski, Grzegorz (Warszawa : Oficyna Wydawn. Rytm, 1997)
The author's essays on contemporary Britain, describing his own visits to the capital and his views on the British Empire.
Keywords: Great Britain -- Description and travel